Development of controlled release particulate system of Melinjo (Gnetum gnemon L.) seed shell extract and effectivity on the hyperuricemic rat model - Eni Masruriati, I Ketut Adnyana, Diky Mudhakir, Heni Rachmawati (Journal of Applied Pharmaceutical Science, 2024)
Melinjo (Gnetum gnemon L), with the active substance resveratrol (RES), is a plant that has the potential to be developed as an anti-hyperuricemic. RES has a limited biological half-life and a short residence time in systemic circulation. This study aims to enhance bioavailability and prolong the anti-hyperuricemic effect with controlled-release matrix formulations. Wet granulation used different hydrophilic matrix (HPMC) K100M and eudragit RSPO amounts as release-controlling polymers to the particulate system. The in vitro release profile of RES was carried out in USP apparatus 3 (reciprocating cylinder) at 10 dpm, using 250 ml of HCl 0.1 N at 37°C ± 0.5°C for 24 hours. The plasma profile of the RES released and the anti-hyperuricemic effect was analyzed. The particulate system had no significant difference in physical properties; they exhibited good physical integrity. HPMC K100M-Eudragit RSPO (F3) released RES longer than pure Melinjo seed shell extract (MSE) and the system without it (F1). The F3 had a better plasma profile of RES, increasing systemic circulation area under curve and t1/2 and extending the anti-hyperuricemic effect. A better effect followed this in lowering serum uric acid levels in the hyperuricemic group. The successful formulation of a particulate system of MSE using HPMC K100M-Eudragit RSPO suggests a promising MSE for hyperuricemia.
Keywords: Gnetum gnemon L., controlled release, particulate system, resveratrol, uric acid, polymer